Genetic code change in at-rich plastid genomes of two holoperasitic plants (balanophoraceae) - Ceriotti, Luis Federico (2019)
The family Balanophoraceae (order Santalales) encompasses 14 genera of obligate root holoparasites (i.e. completely nonphotosynthetic and host-dependent plants). As in other nonphotosynthetic angiosperms, plastid genomes (ptDNA) in Balanophora spp. are characterized by a high degree of reduction in size and gene content, and low levels of GC content. In addition, a novel type of genetic-code change was discovered, in which the TAG codon codes for tryptophan instead of being a stop-codon. In this study, we sequenced and analyzed ptDNA regions of Lophophytum mirabile and Ombrophytum subterraneum (Balanophoraceae). Total DNA from both species was sequenced with Illumina technology. Also, RNAseq was performed for L. mirabile. The ptDNA assembly was carried out based on genomic and transcriptomic paired-end reads. Plastid contigs of L. mirabile and O. subterraneum had an average AT content of 79.55% and 81.75%, respectively. Ribosomal and protein coding genes showed high substitution rates, as in other members of the family. We identified a different change in the genetic code of both ptDNAs; in this case TGA (typically a stop codon) codes for tryptophan. It represents the second case of a genetic-code change in land-plant ptDNAs. RNA editing was not found in the sequenced plastid genes.